PHYSIOTHERAPY MANAGEMENT FOR PATELLAR SUBLUXATION/DISLOCATION: A CASE STUDY - Farida, F; Santosa, Totok Budi; Tiarasani, Ratih (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: This patellar dislocations have been documented up to 43/100,000 and are more common in women than men. There are many other factors as well that can cause a patellar dislocation involving the hip, knee and ankle. Case Presentation: Patients describe the pain that is felt intensity up to 7 of 10 on a Numeric Rating Scale (NRS) scale accompanied by a leg that is unable to bend or straightened. Before coming to physiotherapy, the patient never been treated anywhere except for taking pain relieve. The patient also belongs to the obese category with a BMI value of 31.25 (weight 85kg and height 165cm), the weight factor is also one of the triggered. From the examination carried out with the patient in the supine position and then on palpation it found that there was tenderness, motion pain, local temperature and limitation of motion in the the patient's right knee, the presence of tightness in the knee stabilizer muscles. Active and passive range of motion of the patient's knee joint range of motion is only 0o-20o-35o measured with a Goniometer. Anthropometry is used to measure the swelling, the ratio between the right and left sides. Management and Outcome: This case study it can be concluded that icing, isometric exercise on the quadriceps and hamstrings, and mobilization can reduce pain levels in patients. Stretching and strengthening of the stabilizing muscles of the knee joint coupled with pelvic mobility and walking exercises are able to return the patient's functional activities to normal. Discussion: Some of the training methods provided are considered to provide significant results for patients. From the evaluation results, it was found that there was a decrease in pain as reported by the patient, an increase in ROM in the knee joint, and an improvement in functional activity from the analysis of scores on the womac index. Conclusion: Six therapy sessions applied in this case showed significant results in patients with patellar subluxation/dislocation.